Interaction effects between the 5-hydroxy tryptamine transporter-linked polymorphic region ( 5- HTTLPR) genotype and family conflict on adolescent alcohol use and misuse. - Kim, Jueun; Park, Aesoon; Glatt, Stephen J.; Eckert, Tanya L.; Vanable, Peter A.; Scott-Sheldon, Lori A. J.; Carey, Kate B.; Ewart, Craig K.; Carey, Michael P. (Addiction, 2015)
Aims To investigate whether the effects of family conflict on adolescent drinking differed as a function of 5-hydroxy tryptamine transporter-linked polymorphic region ( 5- HTTLPR) genotype cross-sectionally and prospectively in two independent samples of adolescents. Design Path analysis and multi-group analysis of two prospective datasets were conducted. Settings United States and United Kingdom. Participants Sample 1 was 175 adolescents in the United States (mean age = 15 at times 1 and 2 with a 6-month interval); Sample 2 was 4916 adolescents in the United Kingdon (mean age = 12 at time 1 and 15 at time 2). Measurements In both samples, demographics, tri-allelic 5- HTTLPR genotype and perceived family conflict were assessed at time 1. Alcohol use (frequency of drinking) and alcohol misuse (frequency of intoxication, frequency of drinking three or more drinks, maximum number of drinks) were assessed at times 1 and 2. Findings A significant gene-environment interaction on alcohol misuse at time 1 was found in both sample 1 (β = 0.57, P = 0.001) and sample 2 (β = 0.19, P = 0.01), indicating that the 5- HTTLPR low-activity allele carriers exposed to higher levels of family conflict were more likely to engage in alcohol misuse than non-carriers. A significant gene-environment interaction effect on change in alcohol misuse over time was found only in sample 1 (β = 0.48, P = 0.04) but not in sample 2. Conclusions Compared with non-carriers, adolescents carrying the 5- HTTLPR low-activity allele are more susceptible to the effects of family conflict on alcohol misuse.